2015
DOI: 10.14348/molcells.2015.2240
|View full text |Cite
|
Sign up to set email alerts
|

Comparative N-Linked Glycan Analysis of Wild-Type and α1,3-Galactosyltransferase Gene Knock-Out Pig Fibroblasts Using Mass Spectrometry Approaches

Abstract: Carbohydrate antigens expressed on pig cells are considered to be major barriers in pig-to-human xenotransplantation. Even after α1,3-galactosyltransferase gene knock-out (GalT-KO) pigs are generated, potential non-Gal antigens are still existed. However, to the best of our knowledge there is no extensive study analyzing N-glycans expressed on the GalT-KO pig tissues or cells. Here, we identified and quantified totally 47 N-glycans from wild-type (WT) and GalT-KO pig fibroblasts using mass spectrometry. First,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Because the cornea is an avascular organ, the effect of hyperacute rejection involving alpha Gal is expected to be less than that of a solid organ such as the kidney and heart. In addition, GTKO porcine cornea may increase the expression levels of non-Gal antigens because the level of non-Gal antigens from GTKO porcine fibroblasts is much higher than that from WT porcine fibroblasts ( 64 ). Indeed, elevated levels of non-Gal IgG were reported in rejected GTKO porcine corneas after corneal xenotransplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Because the cornea is an avascular organ, the effect of hyperacute rejection involving alpha Gal is expected to be less than that of a solid organ such as the kidney and heart. In addition, GTKO porcine cornea may increase the expression levels of non-Gal antigens because the level of non-Gal antigens from GTKO porcine fibroblasts is much higher than that from WT porcine fibroblasts ( 64 ). Indeed, elevated levels of non-Gal IgG were reported in rejected GTKO porcine corneas after corneal xenotransplantation.…”
Section: Discussionmentioning
confidence: 99%
“…A higher expression of NeuGc has been demonstrated on GTKO pig tissue (i.e., heart, liver, kidney) and cells (fibroblast cells) compared to NeuGc expression on WT cells, suggesting that deletion of the α1,3-galactosyltransferase gene leads to a ‘compensatory’ increased expression of sialylated glycans, including NeuGc 25,26 . In contrast, in our previous experience we did not document any difference in expression of NeuGc between WT and GTKO pig corneas by immunofluorescence staining 15 .…”
Section: Discussionmentioning
confidence: 99%
“…A study of total N-glycans from membrane glycoproteins, derived from specific pathogen-free miniature pig kidneys, was carried out, and the result showed that α-gal was the most abundant compound among the neutral pig N-glycans. However, the various N-glycan structures of Neu5Gc and Gala1-3Lex epitope as new non-gal carbohydrate antigens were identified by mass spectrometry ( 46 , 63 ). Therefore, non-gal carbohydrate antigens may be the next complication in the transplantation from animals to humans.…”
Section: Clinical Exploitationmentioning
confidence: 99%